THE STRATEGY TO OPTIMIZE THE USE OF BLOCKCHAIN TECHNOLOGY IN DIGITAL SYSTEMS: A CASE STUDY - Sari, Anggi Puspita (Al-Hisab: Jurnal Ekonomi Syariah, 2025)
Early in the twenty-first century, a new phenomena known as "digitalization" emerged, linking technology and civilization while providing clever and practical advantages to humankind. One way to manage zakat money collecting and distribution is for zakat organizations to implement the blockchain idea. The purpose of this study is to present an overview of the potentials, capabilities, and prospects associated with the application of blockchain technology in zakat organizations, particularly in Indonesia. The approach is a literature review, which involves reading a variety of pertinent works and balancing them with similar research on occurrences in other nations. An extensive literature survey on the digitalization of zakat using the blockchain technology was done for this research, which is a descriptive qualitative study. The zakat ecosystem may be further enhanced by the dynamic growth of technology, particularly with the rise of blockchain technology. Blockchain provides the idea of permanent, real-time, safe, and transparent decentralized data.